CATATAN BEBERAPA JAMUR MAKRO DARI PULAU ENGGANO: DIVERSITAS DAN POTENSINYA [Notes on Some Macro Fungi From Enggano Island: Diversity and its Potency] - Retnowati, Atik; Susan, Dewi (BERITA BIOLOGI, 2017)
A Thirty one species of macro fungi which belong to phylum Basidiomycota and Ascomycota were found from three villages in Enggano Island. Among those, nine species are new records for Sumatera, namely Phellinus gilvus, Fomitella supina, Flaviporus liebmannii, Coriolopsis polyzona, Flabellophora sp., Trichaptum byssogenum, Stecherrinum sp., Stereum cf. pergameneum dan Trametes cf. villosa, whilst other two species, namely Cookeina cremeirosea and Fomitella supina are new for Indonesia. One species, Phellinus gilvus, has been known as a harmful parasite on rubber plantation. Six are recognized as edible mushrooms, namely Pleurotus ostreatus, Volvariella volvacea, Schizophyllum commune, Auricularia auricula-judae, Lentinus sajor-caju, and Panus neostrigosus. Two species, Favolus grammocephalus and Panus neostrigosus are therapeutic agents, and two others, Earliella scabrosa and Pycnoporus sanguineus are potential species as color degradation agents.